Penerapan Kemahiran Kebolehgajian terhadap Murid Berkeperluan Pendidikan Khas - Mohamed Yusof, Anizam; Mohd Ali, Manisah; Mohd Noor, Norhayati (Online Journal for TVET Practitioners, 2020)
The purpose of this study is to explore the employability skills that teachers apply to students with special needs in preparation for employment. The design of this study was the case study. Data collection method consisted of interviews which were used as primary data. In addition, content of documents and observations were also used as supporting data. The participants consisted of nine educators from in special education of vocational programs. Thematic analysis technique was used to produce the themes relate to the purpose of research. The findings show that the three main employability skills implemented by teachers are basic skills, workplace competence and entrepreneurial skills. The results of the study are expected to help implement vocational education programs to ensure students with special educational needs are able to meet the requirements of the job market.